The prolonged disruption of a single-course amoxicillin on mice gut microbiota and resistome, and recovery by inulin, Bifidobacterium longum and fecal microbiota transplantation. (October 2020) - Lin, Huai; Wang, Qing; Yuan, Meng; Liu, Lei; Chen, Zeyou; Zhao, Yanhui; Das, Ranjit; Duan, Yujing; Xu, Ximing; Xue, Yingang; Luo, Yi; Mao, Daqing
Abstract: The usages of antibiotics in treating the pathogenic infections could alter the gut microbiome and associated resistome, causing long term adverse impact on human health. In this study, mice were treated with human-simulated regimen 25.0 mg kg −1 of amoxicillin for seven days, and their gut microbiota and resistome were characterized using the 16S rRNA amplicons sequencing and the high-throughput qPCR, respectively. Meanwhile, the flora restorations after individual applications of inulin, Bifidobacterium longum (B. longum), and fecal microbiota transplantation (FMT) were analyzed for up to 35 days. The results revealed the prolonged negative impact of single course AMX exposure on mice gut microbiota and resistome. To be specific, pathobionts of Klebsiella and Escherichia-Shigella were significantly enriched, while prebiotics of Bifidobacterium and Lactobacillus were dramatically depleted. Furthermore, β -lactam resistance genes and efflux resistance genes were obviously enriched after amoxicillin exposure. Compared to B. longum, FMT and inulin were demonstrated to preferably restore the gut microbiota via reconstituting microbial community and stimulating specific prebiotic respectively. Such variation of microbiome caused their distinct alleviations on resistome alteration. Inulin earned the greatest elimination on AMX induced ARG abundance and diversity enrichment. FMT and B. longum caused remove of particular ARGs such as ndm-1, blaPER . Network analysis revealed that most of the ARGs were prone to be harbored by Firmicutes and Proteobacteria. In general, gut resistome shift was partly associated with the changing bacterial community structures and transposase and integron. Taken together, these results demonstrated the profound disruption of gut microbiota and resistome after single-course amoxicillin treatment and different restoration by inulin, B. longum and FMT. Graphical abstract: Image 1 Highlights: Amoxicillin increases the diversity and abundance of ARGs in mice gut microbiota. Amoxicillin has prolonged impact on gut microbiota composition and structure. Inulin and FMT are demonstrated preferably restore the microbiome. FMT and B. longum eliminated particular ARGs including ndm-1 and blaPER. Abstract : This study provided a reference for the effects and countermeasure of amoxicillin on mic gut microbiota and resistome, which may alert us for rational and properly antibiotic use and gut health care supplement.